2021
DOI: 10.18632/aging.203327
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid artery perivascular fat density and cerebral small vessel disease

Abstract: Studies aiming to identify the significance of the carotid artery perivascular fat density are limited. The present study investigated the distribution pattern of pericarotid fat and its association with imaging markers of cerebral small vessel disease (CSVD). In total, 572 subjects who underwent both neck computed tomography angiography and cranial magnetic resonance imaging were analyzed. The pericarotid fat density near the origin of the internal carotid artery (ICA) and imaging markers of CSVD, such as lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Lacunes and WMH are two common MRI markers of CSVD patients ( Xin et al, 2019 ). Zhang et al have reported that an increased pericarotid fat density is associated with the presence of lacunes, and may be linked to CSVD ( Zhang et al, 2021 ). A previous cross-sectional study has provided evidence which linked lacunes and WMHs to a common pathogenesis of CSVD ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lacunes and WMH are two common MRI markers of CSVD patients ( Xin et al, 2019 ). Zhang et al have reported that an increased pericarotid fat density is associated with the presence of lacunes, and may be linked to CSVD ( Zhang et al, 2021 ). A previous cross-sectional study has provided evidence which linked lacunes and WMHs to a common pathogenesis of CSVD ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 In the brain, CAPATd has been associated with the presence and burden of small vessel disease. 31 Small vessel disease is also thought to be associated with increased thrombolytic resistance and bleeding. 32 Furthermore, CAPATd is high in diabetes and metabolic syndrome, possibly correlated with control status for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient's vascular risk factors were also collected, including their hypertension history (blood pressure >140/90 mmHg on admission or previous medical records) [ 11 ], and diabetes mellitus (hemoglobin A1c (HbA1c) ≥ 6.5% or on diabetic medications). Vascular risk factors also include dyslipidemia (serum triglycerides >1.7 mmol/L, low-density lipoprotein >3.4 mmol/L, high-density lipoprotein cholesterol <0.8 mmol/L, or on statins) [ 19 ], current smoking (smoking ≥1 cigarette per day for more than 6 months continuously), and coronary artery disease (history of the previous diagnosis).…”
Section: Methodsmentioning
confidence: 99%